Issues related to Muslim’s willingness in organ donation: perceived Islamic prohibition and the awareness / Liatul Izian Ali Husin, Norfazlina Ghazali and Noorizan Mohamad Mozie - Ali Husin, Liatul Izian; Ghazali, Norfazlina; Mohamad Mozie, Noorizan (UiTM Press, 2018)
Many Malaysian citizens are aware that contributing their organs gives “new life” to the people in need. These little “sacrifices” shows indirectly that Malaysians have high values for their country’s social development. The largest group of ethnicity in Malaysia is Malays. Sadly this ethnic group appears to be the least to sign up as organ donors. In Islam, the allowable of organ donation was not specifically mentioned in the main reference sources which were Quran and Hadith. This is because organ donation was a modern development of medicine in the world. However, many fatwa had been carried out by Muslim scholars. There are many issues contributing to this scenario, among others perceived Islamic prohibition as well as the awareness among muslims themselves. This paper is to grasps insight of these two issues that affect the muslim’s willingness towards organ donation.